IMPLEMENTASI MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR TINGKAT TINGGI (HOTS) SISWA SEKOLAH DASAR - Dwi Poni Egistin; Rizki Ananda; Mufarizuddin; nurhaswinda; Indriyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The weak learning process, students are not actively involved, many students are often sleepy during learning. There are several factors that cause a student's low level thinking ability. Because the learning process in the class is directed to the child's ability to memorize and store up information without being required to understand information and relate it to everyday life. The study was intended to enhance the ipas of class vi primary school (SDN) 033 petapahan, using a creative problem solution (CPS). This type of research is a collaborative class action study. Research design using the models of kemmis and robin McTaggart that include: planning, action, observation, and reflection. The study is carried out in two cycles. The subject of this study is the fourth grade student of 033 land advance board of 24 students. The instrument is a test of high-level thinking ability. The technical data analysis is the quantitative descriptive analysis technique. The results of the study on improving high-order thinking skills (HOTS) using the CPS approach in grade VI students of SD Negeri 033 Petapahan in the 2025/2026 academic year in cycle I, Meeting I, 11 students or 45.83% completed the Very Poor category. In Cycle I, Meeting II, the number of students completing increased to 15 students (62.50%) with the Poor category. Furthermore, in Cycle II, Meeting I, 18 students or 75% achieved completion with the Sufficient category, and in Cycle II, Meeting II, the number of students completing increased to 21 students (87.50%) with the Good category. By implementing the learning stages with the CPS learning model, the application of the Creative Problem Solving (CPS) learning model can improve higher-order thinking skills (HOTS) in elementary school students.